2015
DOI: 10.1016/j.jnci.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of obesity with serum concentrations of leptin, CRP and IL-6 in breast cancer survivors

Abstract: In conclusion, high leptin levels and alteration in acute phase proteins in obese patients may exaggerate the inflammation status. As inflammation has the potential to increase the susceptibility of the patients to metastasis development, it is necessary to decline its rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
2
29
0
4
Order By: Relevance
“…A meta-analysis also confirmed a positive association of leptin with breast cancer [13]. Among breast cancer patients, obesity was associated with higher leptin levels than being overweight or normal weight [14]. Positive association of leptin and breast cancer was limited to post-menopausal women in some studies [15].…”
Section: Genotypingmentioning
confidence: 70%
“…A meta-analysis also confirmed a positive association of leptin with breast cancer [13]. Among breast cancer patients, obesity was associated with higher leptin levels than being overweight or normal weight [14]. Positive association of leptin and breast cancer was limited to post-menopausal women in some studies [15].…”
Section: Genotypingmentioning
confidence: 70%
“…Several studies suggested that exposure to various carcinogens would increase the risk of cancer and the best known among the possible causes of breast cancer development are inflammatory factors, nutritional parameters, obesity and genetic mutations. 5,6 Currently, surgery, radiotherapy (RT), chemotherapy and hormone therapy are effectively used for the treatment of cancer patients. 7,8 RT, as one of commonly used methods for the treatment of cancer, is able to destroy remaining cancer cells after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The level of circulating leptin is proportional to total body fat. Obese patients exhibit high circulating levels of leptin due to leptin resistance[91]. Leptin is a pleiotropic adipokine and pro-inflammatory molecule that belongs to the family of helical cytokines.…”
Section: Leptin and Pcmentioning
confidence: 99%